2021
DOI: 10.1063/5.0039208
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic phase separation model for ternary polymer solutions

Abstract: When a polymer solution undergoes viscoelastic phase separation, the polymer-rich phase forms a network-like structure even if it is a minor phase. This unique feature is induced by polymer dynamics, which are constrained by the temporal entanglement of polymer chains. The fundamental mechanisms of viscoelastic phase separation have already been elucidated by theory and experiments over the past few decades; however, it is not yet well understood how viscoelastic phase separation occurs in multicomponent polym… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The latter aspect is most important because many different nonequilibrium processes such as, e.g., solvent evaporation from a thin film, ,,,,,,, diffusive solvent–nonsolvent exchange, ,, macro- and microphase separation, ,, structure formation in the presence of property gradients ,,, or moving fronts, ,,, hydrodynamic flow, ,, effects of viscoelasticity, ,,, and dynamic arrest due to vitrification, crystallization, or gelation conspire in polymer membrane formation, and the thermodynamic and processing variables span a high-dimensional parameter space that dictates the final nonequilibrium structure. As we have tried to illustrate with the help of selected examples, there has been much progress in each of the individual aspects; however, understanding and predicting their interplay in the course of process-directed macro- and microphase separation during NIPS remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter aspect is most important because many different nonequilibrium processes such as, e.g., solvent evaporation from a thin film, ,,,,,,, diffusive solvent–nonsolvent exchange, ,, macro- and microphase separation, ,, structure formation in the presence of property gradients ,,, or moving fronts, ,,, hydrodynamic flow, ,, effects of viscoelasticity, ,,, and dynamic arrest due to vitrification, crystallization, or gelation conspire in polymer membrane formation, and the thermodynamic and processing variables span a high-dimensional parameter space that dictates the final nonequilibrium structure. As we have tried to illustrate with the help of selected examples, there has been much progress in each of the individual aspects; however, understanding and predicting their interplay in the course of process-directed macro- and microphase separation during NIPS remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This viscoelastic model has recently been generalized to ternary mixtures of polymer, solvent, and nonsolvent. 287 An alternative strategy to account for the slowing down of the kinetics of structure formation in regions of high polymer density consists of employing density-dependent Onsager coefficients. Tree and co-workers 206 employed this technique to model the dynamic arrest upon increase of the polymer density.…”
Section: Particle Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures both inside and on the surface of the film are very important to obtain cooling and superhydrophobic properties. In the preparation process, a phase separation method was adopted to adjust the microstructure of the film. It was found that the ratio of S to EB in SEBS influenced greatly the morphology of the SEBS film, although they have the same chemical structures (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Phase separation of polymer blends and solutions have been a subject of intensive investigations for basic understanding and various applications. Polymers with long chains show a strong segregation trend to form incompatible phases, easily causing the initial homogeneous state to separate into the coexisting phases, which could lead to the feasible fabrication of multiphase particles through phase separation. Microphase separation in the dispersed solvent droplets has been developed to prepare JPs in previous studies. The JPs with “snowman-like” and other morphologies were obtained by using polymers such as polystyrene (PS) and poly­(methyl methacrylate) (PMMA) in toluene droplets, dispersed in aqueous solution with a nonionic surfactant at thermodynamic equilibrium.…”
Section: Introductionmentioning
confidence: 99%